2007
DOI: 10.1038/sj.eye.6703001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between central corneal thickness and the optic disc in an elderly population: the Bridlington Eye Assessment Project

Abstract: Purpose To determine population-based normative CCT data for elderly white subjects, with and without diabetes, and to explore the relationship between CCT and IOP and HRT2 measurements in such subjects with normal visual fields. Methods All eligible subjects were consecutive in a population screened for eye disease. CCT was measured by ultrasound pachymetry, and the optic disc was morphometrically defined using Heidelberg retinal tomography (HRT2). Inclusion criteria were: (1) normal visual field on suprathre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
4
11
1
Order By: Relevance
“…The two variables had a positive, although small relationship. Some studies have suggested that CCT may vary with optic disk size in all eyes or those with POAG29, 36 while other, larger studies evaluating CCT and optic disk size have suggested no relationship31, 37. Our multivariate analysis revealed no relationship between CCT and Global Disk Area in our population when correcting for diagnosis, or in the POAG group alone.…”
Section: Discussioncontrasting
confidence: 55%
“…The two variables had a positive, although small relationship. Some studies have suggested that CCT may vary with optic disk size in all eyes or those with POAG29, 36 while other, larger studies evaluating CCT and optic disk size have suggested no relationship31, 37. Our multivariate analysis revealed no relationship between CCT and Global Disk Area in our population when correcting for diagnosis, or in the POAG group alone.…”
Section: Discussioncontrasting
confidence: 55%
“…None of these associations remained significant after adjusting for age, HRT disc size and IOP (Table 5). This is consistent with the results of a population-based study on normal individuals Hawker et al (2009).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the Tajimi study in Japan found a thinner CCT associated with a larger cup volume [58]. However, in other population-based studies there was no significant relationship with any optic disc parameter [15,59]. Some hospital-based studies have found CCT associated with optic disc area [60][61][62], nasal rim area [63], as well as no significant correlation of CCT and disc size [62].…”
Section: Biological Factorsmentioning
confidence: 92%